Pengaruh Perilaku Keuangan dan Financial Management terhadap Financial Sustainability pada Generasi Z dan Millenial di Kabupaten Bungo - Albadry, Syah Amin; Pratiwi, Widya; Rusnaini, Sasmita; Istianingsih, Nanik; Gonjales, Nana Timorida; Alfiyah, Siti (Jurnal EMT KITA, 2025)
Financial literacy is closely linked to financial management, with increased financial literacy contributing to better personal financial management skills. Personal financial management involves the application of financial principles in individual financial management. Effective financial management, including planning and overseeing financial activities, is crucial for achieving financial stability and economic sustainability. Previous studies indicate that many individuals, particularly Generation Z and Millennials, neglect financial planning and long-term well-being. Without proper financial management, they often face financial difficulties, such as income loss and insufficient emergency funds, which can negatively impact their quality of life. This study involved 100 respondents selected using purposive sampling, with Structural Equation Modeling (SEM) employed to analyze the relationships between the inner and outer models.